Clinical gait features are associated with MRI findings in patients with haemophilic ankle arthropathy. Issue 2 (15th January 2020) - Eerdekens, Maarten; Peerlinck, Kathelijne; Staes, Filip; Pialat, Jean‐Baptiste; Hermans, Cédric; Lobet, Sébastien; Deschamps, Kevin
Abstract: Introduction: Haemophilic ankle arthropathy due to repeated joint bleeds often leads to altered gait in adult patients with haemophilia. Aim: To investigate the association between clinical gait features and blood‐induced ankle joint damage scored using MRI findings in patients with haemophilic ankle arthropathy. Methods: This observational study investigated 48 ankles of 24 patients with severe haemophilia (median age of 33 years). Blood‐induced ankle joint damage was scored by an experienced radiologist using the International Prophylaxis Study Group (IPSG‐)MRI score which evaluates the presence or absence of effusion, synovial hypertrophy, haemosiderin, surface erosions, subchondral cysts and cartilage degeneration. Using 3D gait analysis, peak ankle joint power generation and absorption (W/kg) were measured for each ankle since these are surrogate measures for joint loading during walking. Associations between MRI findings and these two clinical gait features were calculated using Spearman's ρ correlation with an α‐level correction ( α = 0.01) for multiple tests. Results: We found large negative associations between ankle joint peak power generation and IPSG‐MRI score ( ρ = −0.631; P = <.001), IPSG‐MRI osteochondral subscore ( ρ = −0.701; P = <.001), severity of synovial hypertrophy ( ρ = −0.507; P = <.001) and haemosiderin ( ρ = −0.400; P = .005). Associations were also found for ankle joint peak power absorption and IPSG‐MRI score ( ρ = −0.425; P = .003) and IPSG‐MRI osteochondral subscore ( ρ = −0.556; P = <.001). Conclusion: Severe blood‐induced ankle joint damage relates to a lowered tolerance towards ankle joint mechanical loading during walking in patients with haemophilia.